Analysis and Minimization of Waste in The Production Area of PT. XYZ With Lean Manufacturing Approach and System Simulation - Fajriah, Nur; Mahfud, Halim; Hayati, Hayati (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2023)
PT. XYZ is a manufacturing company engaged in the manufacture of packaging cardboard. In the production process at PT. XYZ still found the presence of waste, especially in defects, waiting, and excessive transportation. This study aims to minimize or eliminate waste by providing recommendations for improvement using a lean manufacturing approach, then the improvement recommendations are designed through system simulation using proModel software. The lean manufacturing method used in this research is Value Stream Mapping (VSM) to map the entire value stream in the production process from start to finish, where the VSM manufacturing process is supported based on the tools selected from the Value Stream Analysis Tools (VALSAT). Furthermore, to find the root cause of waste, Fishbone Diagram is used, and to determine the cause of the most critical waste, the Failure Mode and Effect Analysis (FMEA) method is used. The results showed that with the improvement recommendations given, the processing time could be reduced from 9743.70 seconds to 6417.15 seconds, and based on the simulation results the improvement showed an increase in the average number of products per month which was 64.26% with an increase from 52962 pcs to 87000 pcs.